\(15^{23}+19^{23} \equiv (-2)^{23}+2^{23} \equiv -1((-2)^3)-1((2^3)) \equiv 0 \pmod{17}\).
–
Svatejas Shivakumar
·
1 year ago

Log in to reply

@Svatejas Shivakumar
–
Thanks, for the beautiful answer. I was totally perplexed as it was not even solved with Euler's, Fermat, or Wilson's theorem. Now, I see the answer comes just from the basic properties of modular arithematic. Thanks a lottttt!
–
Puneet Pinku
·
1 year ago

## Comments

Sort by:

TopNewest\(15^{23}+19^{23} \equiv (-2)^{23}+2^{23} \equiv -1((-2)^3)-1((2^3)) \equiv 0 \pmod{17}\). – Svatejas Shivakumar · 1 year ago

Log in to reply

– Puneet Pinku · 1 year ago

Thanks, for the beautiful answer. I was totally perplexed as it was not even solved with Euler's, Fermat, or Wilson's theorem. Now, I see the answer comes just from the basic properties of modular arithematic. Thanks a lottttt!Log in to reply